Does modification of portal pressure and flow enhance recovery of the recipient after living donor liver transplantation? A systematic review of literature and expert panel recommendations. Issue 10 (9th December 2022) - Rammohan, Ashwin; Rela, Mohamed; Kim, Dong‐Sik; Soejima, Yuji; Kasahara, Mureo; Ikegami, Toru; Spiro, Michael; Aristotle Raptis, Dimitri; Humar, Abhinav; ,
Abstract: Background: Portal inflow modulation (PIM) aimed at reducing portal hyperperfusion is commonly used in living donor liver transplantation (LDLT) to reduce the risk of small‐for‐size syndrome (SFSS). Many different techniques, both pharmacological and surgical have been used for this purpose. There is, however, little consensus on the best method of PIM, its exact role in preventing SFSS and on early post‐LDLT recovery. Objectives: To identify whether modifications of portal pressures and flows enhance recovery after LDLT and to provide international expert panel recommendations. Data sources: Ovid MEDLINE, Embase, Scopus, Google Scholar, and Cochrane Central. Methods: Systematic review following PRISMA guidelines and recommendations using the GRADE approach derived from an international expert panel. PROSPERO ID: CRD42021260997. Results: Five hundred and ninety four articles were identified through databases' search. Of the 24 included for a final review by the working group (WG), there were five randomized control trials, four prospective studies and 15 retrospective series. Six outcome measures which were likely to influence early recovery after LDLT, especially in small‐for‐size grafts (SFSG) were shortlisted. These included acute kidney injury, SFSS, morbidity including sepsis, length of ICU and hospital stay, morbidity of the PIM technique and overall mortality. The WG noted that PIM in this subset of LDLT recipients had a beneficial effect on all the outcomes measures. Conclusions: Considering all decision domains, the panel recommends pre‐ and intraoperative actual graft weight validation, portal pressure/flow measurements, and a comprehensive donor evaluation for the determination of potentially small‐for‐size/ small‐for‐flow grafts as mandatory. (Quality of Evidence: Moderate | Grade of Recommendation: Strong) Pharmacological PIM helps improve early renal function in LDLT recipients. (Quality of Evidence: High | Grade of Recommendation: Strong) In selected patients with SFSG, PIM helps reduce SFSS/EAD and sepsis. (Quality of Evidence: Moderate | Grade of Recommendation: Strong) PIM in the form of splenectomy has increased morbidity compared to splenic artery ligation (SAL). (Quality of Evidence: Low | Grade of Recommendation: Strong) In LDLT recipients with SFSG, PIM may help reduce morbidity/mortality. (Quality of Evidence: Low | Grade of Recommendation: Strong) In LDLT recipients with SFSG, modification of portal pressures and flows enhances recovery after LDLT. (Quality of Evidence: Moderate | Grade of Recommendation: Strong )